Perbedaan Pengaruh Penggunaan Jurnal Belajar Mind Mapping (JBMM) dan Jurnal Belajar Naratif terhadap Pemahaman Konsep Mahasiswa Calon Guru Biologi pada Mata Kuliah Profesi Kependidikan - Suciati Suciati; Chrisnia Octovi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
This aims of this research is to find out the influenced of using the mind mapping learning journal toward  biology student teachers’ concept understanding  on educational profession subject matter. This research was quasi experimental research with used post-test only nonequivalent control group design. The population of this research was all biology student teachers at semester 2 in Biology Education Department, Faculty of Teacher Training and Education, Sebelas Maret University, 2015/2016 academic years. The sample involved 2 classes, A class consist of 30 students as control class (used the narrative learning journal that is the narrative notes media) and B class consist of 28 students as experiment class (used the mind mapping learning journal. Data collecting used test technique to measure biology student teachers’ concept understanding in educational profession subject matter by using the structured essay test. Non-test technique used observation sheet, interview and documentation as a data of  learning process as well as secondary data. Data Analyze used t-test. The result showed that the average value of concept understanding at A class (81, 00) and B class (84,57) with significance (0,469). Based on the results can be concluded that there was no significant influenced between both of classes.Key Word         : the narrative learning journal, the mind mapping learning journal, concept understanding, educational profession subject matter